Effect of ZnO particles on structural, morphological electrical and dielectric properties of polyaniline (International Journal of Food and Nutritional Sciences, 2022)
In situ chemical oxidation route has been adopted to prepare polyaniline emeraldine salt (PANI) & zinc oxide doped Polyaniline (ZnO/PANI) with different additive weight percent of ZnO using ammonium persulfate (NH4)2S2O8 as an oxidant & HCL as catalyst. Composite of PANI with 10%, 20%, 30%, 40% & 50% of zinc oxide (ZnO) has been synthesized by adding zinc oxide powder gradually in the polymerization solution of aniline & APS. Further these composites were characterized by XRD & SEM techniques to investigate their structural and morphological studies. As a part of electrical studies, AC conductivity, dielectric constant of all the composites were studied as a function of frequency by using impedance analyser. DC conductivity was studied as a function of temperature.